2018
DOI: 10.1021/acs.joc.8b01024
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of the K-Region in a Sterically Hindered Pyrene Carboxamide via Directed Reaction with Alkyllithiums under Air

Abstract: Sterically hindered N,2,7-tri-tert-butylpyrene-1-carboxamide treated with n-BuLi, i-BuLi, s-BuLi, and n-HexLi in THF in the presence of TMEDA and air afforded trans-N,2,7-tri-tert-butylpyrene-10-alkyl-9-hydroxy-9,10-dihydropyrene-1-carboxamides in 63–74% yield. Trifluoroacetic acid promoted dehydration of these compounds gave 10-alkyl derivatives of the starting amide in 79–89% yield. The minor products of this reaction were deamidated compounds, 4-alkyl-2,7-di-tert-butylpyrenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The latter pathway allows the synthesis of a novel polycyclic nitrogen system, aza-benzo[c,d]pyrene (azaolympicene). The obtained results, along with those of our previous studies [28][29][30], show the considerable potential of lithiation of pyrene amides as a tool for functionalization of the pyrene skeleton and synthesis of new fluorophores.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The latter pathway allows the synthesis of a novel polycyclic nitrogen system, aza-benzo[c,d]pyrene (azaolympicene). The obtained results, along with those of our previous studies [28][29][30], show the considerable potential of lithiation of pyrene amides as a tool for functionalization of the pyrene skeleton and synthesis of new fluorophores.…”
Section: Discussionsupporting
confidence: 76%
“…Pyrene readily undergoes aromatic electrophilic substitution reactions (positions 1,3,6, and 8 are particularly reactive) [26,27]. Moreover, the introduction of a secondary amide group at position 1 allowed the lithiation of position 2 [28] and a nucleophilic attack of RLi on the C9-C10 bond (K region) [30]. In this study, we have shown that intramolecular nucleophilic addition to this region with the lithiated N-benzyl fragment is also possible.…”
Section: Synthesis Of 3-9mentioning
confidence: 76%
See 1 more Smart Citation